Raman spectroscopy for early detection and monitoring of dentin demineralization. Issue 12 (December 2020) - Marin, Elia; Hiraishi, Noriko; Honma, Taigi; Boschetto, Francesco; Zanocco, Matteo; Zhu, Wenliang; Adachi, Tetsuya; Kanamura, Narisato; Yamamoto, Toshiro; Pezzotti, Giuseppe
Highlights: For the first time, dentin demineralization has been studied with different spectroscopic techniques. Results from different techniques were successfully correlated. Raman spectroscopy proved to be a good diagnostic tool for evaluation of dentin demineralization. The quantification algorithms can be easily calibrated for in vivo applications. Abstract: Early detection of dental caries and variations in composition/structure of both enamel and dentin represents an important issue in modern dentistry. Demineralization has been associated to teeth discoloration, development of caries, and formation of cavities. Objective: In this study, we systematically monitored the processes of demineralization/remineralization in dentin samples by means of three different spectroscopic techniques, namely, Raman spectroscopy, X-Ray Photo-electron spectroscopy (XPS), and X-Ray Diffractometry (XRD). Methods: Bovine dentin samples were first exposed to acidic solutions and their structure systematically monitored as a function of time and pH. Then, the samples were rinsed in artificial saliva to simulate remineralization. Results: The above three spectroscopic techniques provided quantitative structural information spanning from the nanometer to the millimeter scale of sample penetration depth. An irreversible level of demineralization was reached when dentin was exposed to pH 2 beyond a time threshold of 6 h, successive treatments with artificial saliva being unable to restore the mineral fraction. On the other hand, short-term treatments at pH 5 and long-term treatments at pH 6 could partially or completely recover the dentin structure within one week of remineralization treatment. Significance: Two specific Raman parameters, namely, the bandwidth of the symmetric phosphate-stretching signal and the mineral-to-matrix intensity ratio, showed strong correlations with XPS and XRD data, and matched laser microscopy observations. Such correlations open the path to apply Raman spectroscopy in monitoring dentin demineralization in vivo and provide quantitative working algorithms for the prevention of oral caries.